2022
DOI: 10.1186/s12886-022-02317-x
|View full text |Cite
|
Sign up to set email alerts
|

Status of higher TGF-β1 and TGF-β2 levels in the aqueous humour of patients with diabetes and cataracts

Abstract: Background Transforming growth factor (TGF) is a cytokine that acts on the proliferation, migration, differentiation, and apoptosis of cells and the accumulation of extracellular matrix components. Very few studies have precisely evaluated the concentration of TGF-β in the aqueous humour (AH) of diabetic and cataract (DMC) eyes due to the low expression of proteins in the AH or other reasons. The concentrations of TGF-β1, -β2, and -β3 in the AH of the DMC group were compared with those of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The TGF-β1 pathway is a key to a number of cellular processes, including cell proliferation, migration, and apoptosis [ 32 , 33 ]. It was previously demonstrated that TGF-β1 promotes breast cancer invasion, metastasis, and epithelial-mesenchymal transition by autophagy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β1 pathway is a key to a number of cellular processes, including cell proliferation, migration, and apoptosis [ 32 , 33 ]. It was previously demonstrated that TGF-β1 promotes breast cancer invasion, metastasis, and epithelial-mesenchymal transition by autophagy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…They were found to be associated with various biological processes, such as extracellular matrix organization, positive regulation of transcription from the RNA polymerase II promoter, and positive regulation of the BMP signaling pathway. Noteworthily, some of these processes may be related to the structural components of the lens [ 28 , 29 ]. KEGG pathway analysis further showed that these genes are involved in extracellular matrix-receptor interactions, and in the TGF-β and PI3K/Akt signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…TGFβ is also recognized as a biomarker and significant player in some complications of diabetes [ 24 , 28 , 48 , 49 ]. Likewise, TGFβ1 levels are elevated systemically and in aqueous humor in patients with diabetes [ 50 ] and diabetic retinopathy [ 51 , 52 , 53 ]. Thus, understanding the local cellular response to elevated TGFβ is highly relevant.…”
Section: Discussionmentioning
confidence: 99%